The Importance of Using Movies in EFL Classrooms - Daraselia, Maya; Jojua, Tamar (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The study explores the role of movies in the process of teaching English as a foreign language. The advantages of film-based English learning, the selection of videos and methods of working with them are strongly supported by FL teaching specialists and learners. Watching movies is not only entertainment, but it is also an effective method for teaching and learning a foreign language. Therefore it is possible to combine these two aspects---pleasure and useful teaching/learning activities. Integrating movies in Teaching/learning provides a unique opportunity to help learners immerse in a real language environment. While watching films EFL students can listen to the speech of native speakers, get familiar to different accents and intonation used across various regions where English is spoken, observe gestures and non-verbal expressions. Learners begin to understand better native speakers and eventually will be able to reproduce their speech in more accurate and natural way.Through movies it is possible to learn about the culture and customs of the countrywhere the target language is native, that promotes learners to enhance their languageskills and use them more successfully in oral and written communication.